(3HZjI GdWGdH aj eYQaI GdeaQhV hGdhGLHs - (3GdMdj, GdLfGLj, GdfLaj, ef Bd cGTa GdZWGA, LYaQ Hf NVQ Hf TdGd, J (B1227 (3g`s ((3EHQGgje Hf GdMGL PjH GdeXdhe GdHjWGQ GdYGedjs)
(3ChdgG (B:s
(3GdMeO ddg GdPj CSS bhGYO GdCMcGe(B... (3CeG HYO abO SCdfj LeY ef GdCJbjGA(B... (3hSejJgG HZjI GdWGdH aj eYQaI GdeaQhV hGdhGLHs
(3BNQgG (B:s
(3hJaUjd GdMGd bO eQ aj HjGf CMcGe GdhVhA aQGLYg, hGddg hdj GdJhajb(B... (3Je HYhf Gddgs
(3JHUQI GdYfhGf (B:s
(3aj gOjI GdYGQajf(B: (3ZfjI GdWGdHs
(3JHUQI GdeDda (B:s
(3aj SfI haGJg GNJdGa(B: 1228(3, h(B: 1227(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B2(3, U(B124s
Keywords: (3abg GdePGgH GdCNQis